2011
DOI: 10.1177/0969733011412104
|View full text |Cite
|
Sign up to set email alerts
|

The experience of lying in dementia care

Abstract: This analysis examines the practice of care providers in residential aged care lying to residents with dementia. Qualitative data were collected through multiple methods. Data here represents perceptions from registered and enrolled nurses, personal care assistants, and allied health professionals from five residential aged care facilities located in Queensland, Australia. Care providers in residential aged care facilities (RACFs) lie to residents with dementia. Lying is conceptualized as therapeutic whereby t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 34 publications
6
36
0
4
Order By: Relevance
“…No matter what ethical framework participants used, all suggested that their responses were given in the best interests of the patient. This corroborates a number of previous studies suggesting that lies are used only in the best interests of the person with dementia (Cunningham et al, 2005;Day et al, 2011;Elvish et al, 2010;James et al, 2006;Tuckett, 2012).…”
Section: Ethical Frameworksupporting
confidence: 91%
“…No matter what ethical framework participants used, all suggested that their responses were given in the best interests of the patient. This corroborates a number of previous studies suggesting that lies are used only in the best interests of the person with dementia (Cunningham et al, 2005;Day et al, 2011;Elvish et al, 2010;James et al, 2006;Tuckett, 2012).…”
Section: Ethical Frameworksupporting
confidence: 91%
“…Some authors contend that lying is morally distinct from deception (Benn, 2001;Jackson, 2001), whereas others argue that both acts in clinical practice are ethically akin, because they are both a deliberate abuse of power and an "affront" to patient dignity (Bakhurst, 1992). Whatever the terminology used, empirical studies demonstrate that decision-making about honest communication is a common issue faced by professionals caring for patients with dementia (Day, James, Meyer & Lee, 2011;Elvish, James & Milne, 2010;James, Wood-Mitchell, Waterworth, Mackenzie & Cunningham, 2006;Tuckett, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the nurses and care workers perceived lies and deception to be acceptable in the context of certain interactions with older people with severe dementia. Although the acceptability and ethicality of deception in dementia care remains an area of heated debate, lying is viewed as therapeutic because the care provider's intent is to eliminate harm, control behaviour disorders, and reassure. Deceptive practice has been shown to be prevalent in long‐term care settings.…”
Section: Discussionmentioning
confidence: 99%